Review of islamic criminal law on physical violence committed by teachers against students - Limbong, Idandi; Mukhsin, Abd. (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
The phenomenon of teacher violence in education raises serious concerns because it threatens children’s physical and psychological development. This study aims to examine the limits and forms of physical punishment by teachers that are considered beyond reasonableness in the perspective of Islamic criminal law. Using a qualitative method with a normative juridical approach through library research, data were obtained from classical fiqh works, tafsir, hadith, child protection laws, and relevant academic studies. The analysis employed a normative-analytical framework to compare sharia norms with Indonesian positive law. The findings indicate that violence causing injury, trauma, humiliation, or carried out in anger constitutes jinayah and cannot be justified. Islam only tolerates light discipline (ta’dib) that is educational, painless, and free from emotional motives. The study contributes by showing the alignment between Islamic law and Indonesian positive law in protecting children, while also emphasizing the need for teachers to adopt humanist and moral-based educational approaches supported by legal literacy.